Omzet Comparison Between Offline and Online Selling of Shredded Fish Products in Makassar - A. Padliah Harbah Syamsuddin; Sitti Fakhriyyah; Benny Audy Jaya Gosari; Arie Syahruni Cangara; Andi Amri (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
This study aims to compare the omzet between offline and online sales in the shredded fish business unit in Makassar. This research lasted for two months using qualitative and quantitative research types with a purposive method in sampling. This research uses observation, interview, and literature study techniques in data collection methods and acceptance formulas for calculating quantitative data. The data used in this study are primary data that is data obtained after conducting interviews with three shredded fish business units in Makassar, interviews conducted related to offline and online sales efforts conducted by each business unit and secondary data obtained from the results report sales and literature that supports research from three shredded fish business units in Makassar. Based on the results of the study showed an average offline sales turnover of Rp 3.772.000 and online sales of Rp 24.132.430, where offline only uses production sites and entrusted to sell in stores, while online uses the application WhatsApp, Facebook, Instagram, Gojek, and Grab so that the wider market reach.